Spectroscopy with Chemometrics for the Forensic Analysis of Sandy Soils - Newland, Talia Grace (Curtin University, 2023)
This thesis explores the objective characterisation and differentiation of arid, sandy, soil samples for forensic purposes through a multi-faceted approach that utilises spectroscopic techniques in combination with chemometrics. The findings demonstrate the potential value of sandy soils when used for site discrimination within a forensic context and lay the groundwork for increased use of this form of evidence in forensic laboratories in jurisdictions with similar soils.